GAYA BAHASA PASAMBAHAN ADAT PERKAWINAN DI DESASUNGAI LIKU KENAGARIAN PELANGAI KECAMATAN RANAH PESISIR KABUPATEN PESISIR SELATAN - Hasmi Novianti (Jurnal Kepemimpinan dan Pengurusan Sekolah, 2017)
This research is motivated by the diversity of style language used by a person to communicate and express thoughts, feelings, opinions, ideas and concepts, both in the form of speech (oral) and in print. Style language used by speakers of languages ​​using a style that is beautiful and attractive, especially pasambahan. The focus of this research is stylistic pasambahan manjapuik marapulai in the village of Sungai Liku. The purpose of this study is to describe in detail and clearly about the style of the language contained in manjapuik pasambahan marapulaiin the village of Sungai Liku. This type of research is qualitative. The object of research is a script pasambahan manjapuik marapulai previously transcribed from the recording pasambahan manjapuik marapulai. The informant in this research that people who are directly involved in pasambahan.. Examination of the data validation performed in this study with a degree of confidence (credibility) by using 2 techniques, namely; increase endurance, member check and use of reference materials. Based on the interpretation of the data that has been done to pasambahan manjapuik researchers marapulai in Sungai Liku Village Kenagarian PelangaiPesisir Selatan District of Ranah Pesisir cone, found some kind of style. First, the comparison language style as much as three types.